PSIKOLOGI TOKOH FANTON DRUMMOND DALAM NOVEL OLENKA KARYA BUDI DARMA TAHUN PELAJARAN 2012/2013 - Solanda, Marfia; Bahardur, Iswadi; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2013)
This research is distributed by the conflict in and around the maze of life of a character named Fanton Drummond are often faced with a less supportive environment desires. Formulation of this research is